Explaining cosmological anisotropy: evidence for causal horizons from CMB data. Issue 4 (30th April 2021) - Fosalba, Pablo; Gaztañaga, Enrique
ABSTRACT: The origin of power asymmetry and other measures of statistical anisotropy on the largest scales of the universe, as manifested in cosmic microwave background (CMB) and large-scale structure data, is a long-standing open question in cosmology. In this paper, we analyse the Planck Legacy temperature anisotropy data and find strong evidence for a violation of the Cosmological principle of isotropy, with a probability of being a statistical fluctuation of the order of ∼10 −9 . The detected anisotropy is related to large-scale directional ΛCDM cosmological parameter variations across the CMB sky, which are sourced by three distinct patches in the maps with circularly averaged sizes between 40° and 70° in radius. We discuss the robustness of our findings to different foreground separation methods and analysis choices, and find consistent results from WMAP data when limiting the analysis to the same scales. We argue that these well-defined regions within the cosmological parameter maps may reflect finite and casually disjoint horizons across the observable universe. In particular, we show that the observed relation between horizon size and mean dark energy density within a given horizon is in good agreement with expectations from a recently proposed model of the universe that explains cosmic acceleration and cosmological parameter tensions between the high- and low-redshift universe from the existence of casual horizons within our universe.